Analysis Of Judicial Considerations In Imposing Sanctions On Perpetrators Of Domestic Violence (DV) (A Study of Court Decision Number: 544/Pid.Sus/2025/PN Tjk) - Zainab Ompu Jainah; Dony Tri Rinaldo. (Cita konsultindo, 2026)
Cases of Domestic Violence (DV) as reflected in Court Decision Number 544/Pid.Sus/2025/PN Tjk illustrates how violence within the household sphere can develop into a criminal case that must be resolved judicially through proceedings. The research problems addressed in this study are the factors causing the occurrence of Domestic Violence (DV) crimes and the judicial considerations in imposing sanctions on perpetrators of Domestic Violence (DV) based on Court Decision Number 544/Pid.Sus/2025/PN Tjk. The research method employed is a normative juridical approach combined with an empirical approach, and the conclusions are drawn using deductive reasoning to provide a general overview of the answers to the research problems based on the findings of the study. The results of the study indicate that Domestic Violence (DV) crimes are influenced by multidimensional factors, such as economic conditions, inability to control emotions, unequal power relations, and patriarchal culture, which are exacerbated by the victim's economic and psychological dependence and low level of legal awareness. A victimological perspective shows that victims of DV are in a weak and vulnerable position, indicating that DV is a social problem requiring state intervention. Based on Court Decision Number 544/Pid.Sus/2025/PN Tjk, judges impose sanctions by considering juridical, sociological, and philosophical aspects, including the physical and psychological impacts suffered by victims, in order to achieve deterrence, justice, and legal protection for victims of Domestic Violence. Recommendations suggest that law enforcement officers, the government, and the community need to strengthen efforts to prevent Domestic Violence through legal education, increased awareness of equality within households, and economic and psychological protection for victims. Inter-institutional synergy and preventive–rehabilitative approaches are essential to break the cycle of violence. Judges, in deciding Domestic Violence cases, are expected to prioritize victim protection and substantive justice by considering the sociological and psychological aspects of victims and applying a victimological perspective, so that court decisions provide not only legal certainty but also maximum protection for victims.